2015
DOI: 10.1519/jsc.0000000000000776
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Two Generic Aerobic Interval Training Methods on Laboratory and Field Test Performance in Soccer Players

Abstract: The purpose of this study was to compare the effects of 2 generic aerobic training models, based on peak running velocity in Carminatti's test (PVT-CAR) in U-20 elite soccer players. Seventeen soccer players (age: 17.9 ± 1.0 years; 178.6 ± 5.0 cm; 73.6 ± 6.6 kg; 11.1 ± 1.3%) from a team competing in a national junior league took part in the study. The athletes performed a series of pre- and posttraining tests (incremental test on a treadmill to determine the maximal oxygen uptake [(Equation is included in full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 27 publications
5
26
1
1
Order By: Relevance
“…Previous studies have already shown that efforts lasting ≈ 2 to 4 min at an intensity near to maximal or maximal (e.g. 100%PVT-CAR) are capable to induce a high cardiovascular demand (Da Silva et al, 2015; Ferrari Bravo et al, 2008; Helgerud et al, 2001; Laursen et al, 2004), being an effective approach to improve the cardiorespiratory and metabolic function, and, in turn, to enhance the athletes physical performance (Ferrari Bravo et al, 2008; Helgerud et al, 2001; Impellizzeri et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have already shown that efforts lasting ≈ 2 to 4 min at an intensity near to maximal or maximal (e.g. 100%PVT-CAR) are capable to induce a high cardiovascular demand (Da Silva et al, 2015; Ferrari Bravo et al, 2008; Helgerud et al, 2001; Laursen et al, 2004), being an effective approach to improve the cardiorespiratory and metabolic function, and, in turn, to enhance the athletes physical performance (Ferrari Bravo et al, 2008; Helgerud et al, 2001; Impellizzeri et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the HR and peak velocity derived from intermittent field testing are the two most commonly measured physiological markers used for prescribing and controlling exercise intensity in the field conditions (Buchheit and Laursen, 2013). For instance, Fernandes da Silva et al (2015) showed that training with and without direction change at the intensity of the 100%PVT-CAR was effective in improving aerobic power and capacity, and the ability to perform high-intensity intermittent activities in U-20 elite soccer players. Furthermore, Ferrari Bravo et al (2008) and Helgerud et al (2001) demonstrated that 4 sets of 4 min at 90-95% of the HRmax with 3 min of active recovery at 60-70% of the HRmax were efficient training stimuli to increase the cardiorespiratory function and soccer performance (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 As leg muscle is employed in jump, kick, tackle, turn, speeding, and turn, enhancement in its strength is relevant to improvement of such skills. 8 Foundation for explosive movement lies in leg muscular strength and leg muscular power has much impact on game performance. 9 Balance can be classified into static balance and dynamic balance.…”
Section: Introductionmentioning
confidence: 99%